Proteasomal proteolysis in p62 condensates directs tumor suppression or growth depending on their subcellular localization - Chen Lulu-Shimron; Zhiwen Luo; Vera Brekhman; Lina Huang; Ido Livneh; Hidetaka Kosako; Victoria Cohen-Kaplan; Aaron Ciechanover (Proceedings of the National Academy of Sciences, 2026)
p62/SQSTM1 generates liquid–liquid phase-separated condensates that participate in diverse processes, including protein quality control (PQC) and autophagy. Nuclear p62 condensates were shown to act as ubiquitin- and proteasome-mediated degradation hubs, whereas the involvement of cytoplasmic condensates in this pathway has remained unclear. Here, we show that cytoplasmic p62 condensates serve as a hub for proteasomal degradation that displays distinct substrate preferences compared with nuclear condensates. Specifically, cytoplasmic condensates mediate accelerated degradation of the tumor suppressor p53 through recruitment MDM2, its E3 ligase, while nuclear condensates are selectively enriched with USP7, a deubiquitinating enzyme (DUB) that stabilizes p53. Immunohistochemical analysis of human tissues reveal that p62 in healthy tissues is largely localized to the nucleus, whereas in the corresponding malignant tissues, it is largely in the cytosol, which is correlated with reduced p53 abundance in tumors. Nuclear p62 condensates also promote the degradation of oncogenic c-Myc, underscoring compartment-specific differences in protein turnover. Experiments in cancer cells and xenografts demonstrate that cytoplasmic p62 condensates drive tumor growth, whereas nuclear p62 condensates suppress it. Moreover, condensate formation rather than p62 expression alone is required for both enhanced proteolytic activity and tumor growth modulation. Proteomic analysis reveals that nuclear p62, unlike its cytosolic counterpart, is linked to enrichment of proteins associated with apoptosis, p53 stabilization, DNA damage response, and cellular senescence—all related to tumor suppression. These findings establish that p62 condensates provide compartment-specific regulation of ubiquitin and proteasomal degradation and suggest that manipulating their localization or affecting their dynamics can offer different therapeutic opportunities.